2017
DOI: 10.2519/jospt.2017.7057
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Recreational Physical Activity in Patients With Chronic Low Back Pain: A Pragmatic Controlled Clinical Trial

Abstract: Study Design Prospective, pragmatic, nonrandomized controlled clinical trial. Background Clinical guidelines recommend physical activity for the treatment of chronic low back pain. But engaging patients in physical activity has proven difficult. Known obstacles to physical activity include low self-efficacy and fear avoidance. Objectives This study tested the effectiveness of an enhanced transtheoretical model intervention (ETMI) aimed at increasing recreational physical activity in patients with chronic low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 43 publications
3
60
1
Order By: Relevance
“…Additionally, this review only included interventions with an exercise prescription, and not general PA. PA, such as walking (O'Connor et al, 2015) and habitual PA (Ben-Ami et al, 2017), have been found to decrease pain in this population. Future reviews should further explore adherence to PA interventions in a population with PMSK.…”
Section: Methodological Considerationsmentioning
confidence: 83%
“…Additionally, this review only included interventions with an exercise prescription, and not general PA. PA, such as walking (O'Connor et al, 2015) and habitual PA (Ben-Ami et al, 2017), have been found to decrease pain in this population. Future reviews should further explore adherence to PA interventions in a population with PMSK.…”
Section: Methodological Considerationsmentioning
confidence: 83%
“…The format of delivery of the behavioural counselling interventions varied between trials (Table ). In four trials (Ben‐Ami et al, ; Friedrich et al, ; Lonsdale et al, ; Vong et al, ), behavioural counselling was delivered in conjunction with physiotherapy. Behavioural counselling was also delivered alongside a prescribed exercise routine including supervised exercise sessions (Ang et al, ), with occupational therapy (Niedermann et al, , ) and with cognitive behavioural therapy (Kerns et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…PA and home exercise completion was measured in nine trials (Table ). PA was measured using only self‐reported questionnaires in seven trials (Allen et al, ; Ben‐Ami et al, ; Friedrich et al, ; Knittle et al, , ; Lonsdale et al, ; Vong et al, ; Williams et al, ), both a self‐reported questionnaire and accelerometry in one trial (Ang et al, ) and accelerometry only in one trial (Gilbert et al, ). Where multiple self‐reported measures were used, time duration was the most commonly used unit of measure.…”
Section: Resultsmentioning
confidence: 99%
“…In future studies and clinical application of PA&E as treatment, it is therefore interesting to further emphasize behavioural strategies for increased adherence to the prescribed PA&E, separate from and parallel to behavioural approaches focusing on the chronic pain. This speculation of the importance of behavioural strategies to enhance adherence to prescribed PA&E is in line with the conclusion in paper 4, and to the results of one recent study showing improved adherence to recreational PA&E as well as improved pain related outcomes when behaviour change strategies were included in the intervention design [245].…”
Section: Discussionsupporting
confidence: 69%
“…PA&E are health behaviours. However, health behaviour change theories are surprisingly rarely included in studies on PA&E as treatment for chronic pain, even though recently one study reports relations between core constructs within the SDT and the Theory of Planned Action applied on individuals with chronic pain [239], and one study showed that interventions based on the Transtheoretical Model [244] increased recreational PA&E in patients with chronic low back pain [245].…”
Section: Discussionmentioning
confidence: 99%